2008
DOI: 10.1007/bf03321592
|View full text |Cite
|
Sign up to set email alerts
|

Long-term predictive value of salivary microbial diagnostic tests in children

Abstract: Children whose mouths were colonized by salivary lactobacilli at baseline were more susceptible to caries onset in both primary and permanent molars at any given time during follow- up of seven years than children who were not colonized by those caries associated microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Candida albicans is the most commonly isolated candida species in the oral cavity and constitute up to 80% of the clinical isolates [20]. Furthermore, candida has been ascribed a significant predictive value for dental caries in children [21]. The majority of the lactobacilli strains were fully identified with biochemical analysis using the API 50 CH system while a satisfactory identification of the L .…”
Section: Discussionmentioning
confidence: 99%
“…Candida albicans is the most commonly isolated candida species in the oral cavity and constitute up to 80% of the clinical isolates [20]. Furthermore, candida has been ascribed a significant predictive value for dental caries in children [21]. The majority of the lactobacilli strains were fully identified with biochemical analysis using the API 50 CH system while a satisfactory identification of the L .…”
Section: Discussionmentioning
confidence: 99%
“…This was attributed to its acidogenicity, capabilities of forming hyphae and the secretion of dentine‐degrading enzymes . Some studies support a significant association between dental caries and the presence and levels of C. albicans in saliva . A study following 183 children over 7 years showed that early colonization with Candida was associated with caries onset in primary molars, but not in permanent first molars .…”
Section: Microorganisms In Saliva As Biomarkers Of Cariesmentioning
confidence: 99%
“…Some studies support a significant association between dental caries and the presence and levels of C. albicans in saliva . A study following 183 children over 7 years showed that early colonization with Candida was associated with caries onset in primary molars, but not in permanent first molars . In some other studies, however, association between caries and Candida was not supported .…”
Section: Microorganisms In Saliva As Biomarkers Of Cariesmentioning
confidence: 99%
“…Recently, C. albicans has been shown to cause caries (Nikawa et al, 2003). Streptococcus mutans, lactic acid bacteria, and actinomycetes have traditionally been recognized as the main factors causing caries bacteria in the oral cavity; however, C. albicans is frequently present in caries-active groups, and the rate of detection of C. albicans in the oral cavity is much higher than that in those who are caries-free (Ollila and Larmas, 2008;Raja et al, 2010). C. albicans has been detected in children's dentine caries at a rate of 71-97% (de Carvalho et al, 2006), indicating the importance of this pathogen in causing caries.…”
Section: Introductionmentioning
confidence: 99%